Implementation of E-consent in infectious & isolated patients: a novel cost-conserving technique - Tse, Gerald; Tay, Yoong Chuan (International Journal of Infection Control, 2025)
Background: The COVID-19 pandemic highlighted the need for innovative solutions to enhance infection prevention and control measures in healthcare settings, particularly for infectious and isolated patients. Objective: To describe the implementation of a novel cost-conserving electronic procedural consent technique in infectious and isolated patients during the COVID-19 pandemic. Design: During the COVID-19 pandemic, we implemented an electronic consent technique using pre-existing hardware in the form of Toughbook tablets with styluses, and biohazard-grade ziplock bags. We trialled this method on patients with confirmed or suspected COVID-19 requiring surgery. Results: This e-consent system was used in 83 patients undergoing surgery. Benefits included effective sanitization of the Toughbooks and the low cost. Challenges included suboptimal signature accuracy and the need for a back-up method when the Toughbook malfunctioned, or where e-signatures could not be obtained. The system was discontinued as the pandemic and isolation measures eased. Discussion: The e-consent system provided a practical solution during the pandemic, reducing physical contact and supporting infection control. While effective, challenges related to technology and patient adaptability remained. The system demonstrated potential for broader applications, including in telemedicine and isolation care, but requires further evaluation in high-volume settings. Conclusions: E-consent effectively minimized the risk of infection transmission and improved consent workflows. Beyond the pandemic, e-consent offers long-term benefits in infection prevention, consent management, and remote access, supporting safer, more flexible patient care across clinical settings. However, further studies are needed to evaluate its impact on reducing infection transmission and personal protective equipment (PPE) waste.